Lemmel’s syndrome: a case report with insights from a literature review on diagnosis and management - Salma El Aouadi; Kaoutar Imrani; Salma Tabati; Majda Ankri; Ihssane lahlou; Nabil Moatassim Billah; Ittimade Nassar (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background First described in 1934, Lemmel’s syndrome is a rare condition caused by the extrinsic compression of the distal common bile duct due to a periampullary duodenal diverticulum, in the absence of choledocholithiasis or pancreatobiliary tumors. Cross-sectional imaging is useful for diagnosing this condition noninvasively, helping to rule out other pathologies in the peri-ampullary region. Case presentation We present a case of a 74-year-old female who presented with abdominal pain, jaundice, and elevated bilirubin and liver enzymes. Imaging revealed a periampullary diverticulum compressing the distal bile duct, consistent withLemmel’s syndrome. Conclusions This case underscores the importance of imaging modalities such as CT and MRCP in diagnosing Lemmel’s syndrome and differentiating it from other periampullary conditions. A literature review of 46 cases highlights the spectrum of diagnostic challenges and treatment options, ranging from conservative management to endoscopic and surgical interventions.